Effect of Pregnancy and the Postpartum Period on Adherence to Antiretroviral Therapy Among HIV-Infected Women Established on Treatment. (1st April 2015) - Henegar, Cassidy E.; Westreich, Daniel J.; Maskew, Mhairi; Miller, William C.; Brookhart, M. Alan; Van Rie, Annelies
Abstract : Abstract: Among women who become pregnant after initiating highly active antiretroviral therapy (HAART), few data describe the effect of pregnancy and postpartum on adherence. We conducted a retrospective clinical cohort study among therapy-naive women (age, 18–45 years) initiating HAART in Johannesburg, South Africa. Among 7510 women in our analysis, 896 experienced a pregnancy after starting HAART. Compared with nonpregnant periods of follow-up, there was an increased risk of nonadherence during the postpartum period (weighted risk ratio: 1.46, 95% confidence interval: 1.17 to 1.82) but not during pregnancy itself (weighted risk ratio: 0.95, 95% confidence interval: 0.78 to 1.17).